Design and implementation of a mentoring program for postgraduate students: a case study of qualitative analysis mentoring - Mohamad, Ani Munirah; Mustafa, Eshaby; Mohd Arshad, Ain Husna; Mohd Ariffin, Nurhazlina; Syed Mahmood, Syarifah Rohaniah (RSIS International, 2025)
A well-designed mentoring program is found to be highly facilitative for postgraduate students. The process of supervision is normally related to the main contents of research. Therefore, a mentoring program may provide an opportunity for the postgraduate students to develop skills that are normally not acquired from supervision. This paper discusses the twelve-steps process in designing and implementing a mentoring program for postgraduate students. Case study design was employed in this research, focusing on a qualitative analysis mentoring program conducted at one of the higher learning institutions in Malaysia, with specific reference to computer-assisted qualitative data analysis software known as ATLAS.ti. The discussion includes stages of mentoring on the use of ATLAS.ti for qualitative data analysis process. It is found that the mentoring on the use of computer-assisted software, particularly ATLAS.ti, has been able to facilitate students’ understanding on the process of qualitative data analysis. Future research could be conducted to larger scale population and the mentoring of different software so as to generalize the findings of the study. Hopefully this paper will become a focal reference for similar mentoring programs for other areas and topics in the future